Promoting urban ecological resilience through the lens of avian biodiversity - McCloy, Michael W. D.; Andringa, R. Keith; Maness, Terri J.; Smith, Jennifer A.; Grace, Jacquelyn K. (Frontiers in Ecology and Evolution, 2024)
The significance of urban landscapes in safeguarding biodiversity is often disregarded, even though a considerable amount of conservation focus is directed toward biodiversity hotspots where urban land conversion is happening at the fastest pace. Maintaining biodiversity in urban areas not only benefits the environment, but along with social, economic, and technological factors can increase the stability of urban systems to disturbance, a concept known as “urban resilience”. In this synthesis paper, we explore the ecological dimension of urban resilience and specifically focus on avian biodiversity because birds are easy to observe, relatively abundant, and can serve as an indicator of the overall health of urban environments. We first examine the concept of ecological resilience and discuss the role of environmental stressors associated with urbanization in the ongoing avian biodiversity crisis. We then provide an overview of characteristics of the urban environment that may promote ecological resilience in birds, and associations between social and economic factors and urban ecological resilience. Finally, we provide recommendations on future research regarding strategies to improve urban ecological resilience and thus, urban resilience as a whole, at the intersections of urban ecology, ecosystem ecology, environmental justice, and urban planning. Since 68% of the world's population is projected to live in urban areas by 2050, it is imperative that scientists, urban planners, civil engineers, architects, and others consider urban ecological resilience as a dimension of both environmental health and the resilience of cities to future natural and anthropogenic disasters.